Proceedings of the 38th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2005.284
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Deception and Its Detection Under Varying Electronic Media Conditions

Abstract: Studies have shown that deception in the hiring process is common.Since more people are using computer mediated communication for job interviewing, it is important to understand how those modes of communication affect deception and its detection. Differences in gender may affect the communication process. Very little research has been conducted on gender and deception via electronic media. This paper presents hypotheses concerning gender differences in deception and detection in job interviewing situations usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…(Kaina et al, 2011) found that females are more easily detectable when lying than their male counterparts. (Tilley et al, 2005) reported that females are more successful in deception detection than male receivers.…”
Section: Related Workmentioning
confidence: 99%
“…(Kaina et al, 2011) found that females are more easily detectable when lying than their male counterparts. (Tilley et al, 2005) reported that females are more successful in deception detection than male receivers.…”
Section: Related Workmentioning
confidence: 99%
“…Published by Cambridge University Press. As many studies suggest, deception is an act that depends on many factors such as personality (Fornaciari et al 2013;Levitan et al 2015), age (Sweeney and Ceci 2014), gender (Tilley et al 2005;Toma et al 2008;Fu et al 2008), or culture (Taylor et al 2014;Taylor et al 2017;Leal et al 2018). All these factors affect the way and the means one uses to deceive.…”
Section: Introductionmentioning
confidence: 99%
“…The number of interpreting cues is fewer, because message recipients neither see nor hear the sender. The disconnect between recipients and senders precludes access to visual cues (facial expressions, gestures) and vocal cues (voice tones) that may be useful for interpreting message content and for understanding the intent of message senders (e.g., Tilley et al 2005). The result may be diminished decision-making quality (e.g., Kahai and Cooper 2003).…”
Section: Introductionmentioning
confidence: 97%